Univerzitní repozitáře ve Skandinávii: současný stav a perspektivy jejich rozvoje - Žvátorová, Veronika (Univerzita Karlova, Filozofická fakulta, 2008)
Defended thesis about university institutional repositories in Scandinavia freely accesible over the Internet brings theoretical and practical overview and description of this subject. Thesis is divided into two main parts. Theoretical part describes the most important information about development, progress and running of institutional repositories in general. This part is focused on basic questions, whose are necessary for good comprehension of repositories throughout the world. Part of this section contains description about open access, copyright and appropriate software. Practical part then contains analysis of eight Scandinavian repositories. These are: Danish Roskilde University Digital Archive (http://rudar.ruc.dk/), Finnish archive Teknillisen korkeakoulun elektroniset väitöskirjat, eng. TKK electronic academic dissertations (http://lib.tkk.fi/Diss/), Icelandic archives Landspítali University Hospital research archive Hirsla (http://lsh.openrepository.com/lsh/) and repository of University of Akureyri and Icelandic University of Education Skemman (http://skemman.khi.is/), Norwegian archive Center for European studies on University of Oslo ARENA Publications (http://www.arena.uio.no/publications/) and Norwegian repository Publications from Norwegian University of science and technology. Obhajovaná rigorózní práce popisuje teoretickým i praktickým způsobem současný stav univerzitních institucionálních repozitářů volně dostupných na Internetu. Jádro práce je zaměřeno na tento typ elektronických archivů ve Skandinávii. Rigorózní práce je rozdělena na hlavní dvě části, které přinášejí poznatky o provozu univerzitních repozitářů. Teoretický úvod shrnuje nejdůležitější otázky z oblasti budování a rozvoje institucionálních repozitářů obecně. Tato část není omezena geograficky a osvětluje základní pojmy nutné pro pochopení fungování institucionálních repozitářů v celosvětovém záběru. Nedílnou součástí jsou otázky otevřeného přístupu, autorskoprávní problematiky a vhodného software pro praktický provoz ...